Thrombosis of the deep veins of the leg. Iterative pulmonary embolisms. Surgical interruption of the common femoral vein. healing - Suiffet, Walter; Musso, R. (Cirugía del Uruguay, 2020)
Presented in Session of June 26th, 1946.